Differences in F pocket impact on HLA I genetic associations with autoimmune diabetes - Ren, Xu; Amarajeewa, A. W. Peshala; Jayasinghe, M. D. Tharushika; Garstka, Malgorzata A. (Frontiers in Immunology, 2024)
Human leukocyte antigen (HLA) I molecules present antigenic peptides to activate CD8+ T cells. Type 1 Diabetes (T1D) is an auto-immune disease caused by aberrant activation of the CD8+ T cells that destroys insulin-producing pancreatic beta cells. Some HLA I alleles were shown to increase the risk of T1D (T1D-predisposing alleles), while some reduce this risk (T1D-protective alleles). Here, we compare the T1Dpredisposing and T1D-protective allotypes concerning peptide binding, maturation, localization and surface expression and correlate it with their sequences and energetic profiles using experimental and computational methods. T1D-predisposing allotypes have more peptide-bound forms and higher plasma membrane surface levels than T1Dprotective allotypes. This was related to the fact that position 116 within the F pocket is more conserved and make more optimal contacts with the neighboring residues in T1D-predisposing allotypes than in protective allotypes. Our work uncovers that specific polymorphisms in HLA I potentially influence their susceptibility to T1D.